2019
DOI: 10.3390/atmos10040171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Meteorological and Hydrological Memory on Compound Peak Flows in the Rhine River Basin

Abstract: Spatio-temporal variation of hydrological processes that have a strong lagged autocorrelation (memory), such as soil moisture, snow accumulation and the antecedent hydro-climatic conditions, significantly impact the peaks of flood waves. Ignoring these memory processes leads to biased estimates of floods and high river levels that are sensitive to the occurrence of these compounding hydro-meteorological processes. Here, we investigate the role of memory in hydrological and meteorological systems at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…The Rhine is one of the largest river basins in Western Europe and is intensively used for agriculture, industry, and navigation (Kwadijk & Rotmans, 1995; Van Alphen, 2016). The basin area is 185,000 km 2 with 58 million inhabitants of which more than 10 million live in flood‐prone areas (ICPR, 2001; Khanal et al, 2019). The river originates in the Swiss Alps and flows along the Southern boundary between France and Germany and continues through Germany before it enters the Netherlands at Lobith (Te Linde et al, 2011; van Osnabrugge et al, 2017; Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Rhine is one of the largest river basins in Western Europe and is intensively used for agriculture, industry, and navigation (Kwadijk & Rotmans, 1995; Van Alphen, 2016). The basin area is 185,000 km 2 with 58 million inhabitants of which more than 10 million live in flood‐prone areas (ICPR, 2001; Khanal et al, 2019). The river originates in the Swiss Alps and flows along the Southern boundary between France and Germany and continues through Germany before it enters the Netherlands at Lobith (Te Linde et al, 2011; van Osnabrugge et al, 2017; Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Every year on average two strong storm events (winds higher than 19-20 m/s) are recorded at Hoek van Holland (Smits et al, 2005). Further, these depression systems are also characterized by humid Atlantic moisture conditions and primarily transport the moisture toward the Netherlands (Khanal et al, 2019).…”
Section: North Seabmentioning
confidence: 99%
“…The associated impacts strongly depend on the catchment features and the characteristics of the storms (Wahl et al, 2015). For discharge peaks originating from remote precipitation or snowmelt inputs (for instance in larger river systems), delays between the surge and discharge peaks are usually due to the finite travel speed of the discharge wave (Khanal et al, 2019b;Klerk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using SMILEs is a physically based approach to increase the size of the database and therefore increase the number of simulated extreme compound events. Apart from van den Hurk et al (2015), SMILEs have been applied as a tool to investigate compound events by, for example, Zhou and Liu (2018), Khanal et al (2019a), andPoschlod et al (2020). This methodology allowed van den Hurk et al (2015) to demonstrate a positive dependence between storm surge and heavy precipitation and showed that the probability of occurrence of these extreme water levels can be greatly underestimated if such dependence is omitted.…”
Section: Introductionmentioning
confidence: 99%